Penanaman Nilai Karakter Religius dan Disiplin pada Siswa SD Melalui Kegiatan Shalat Dhuha - Subandryo, Subandryo; Faoji, Ahmad; Syahrani, Jihan Fitri (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
In this modern era, character values ​​are needed to prevent and treat moral crises due to advances in technology and information. The aim of the research regarding implanting religious and discipline character values ​​in elementary school students through Dhuha prayer activities is to identify the process and obstacles in implanting religious and discipline character values ​​in students through Dhuha prayer activities, as well as the impact of Dhuha prayer activities on students' religious and discipline character. Researchers used a qualitative approach and case study research methods. The data collection techniques used were observation, interviews and documentation. The research results obtained; the Dhuha prayer activity has a positive impact on the religious and discipline character values ​​of students at the school, as seen by observation, interviews, and documentation indicates that students became accustomed to religious worship and understood the importance of being close to Allah, and became more disciplined in following school rules and routines.